Hormone affinity and fibril formation of piscine transthyretin: the role of the N-terminal - Morgado, Isabel (2014)
Transthyretin (TTR) transports thyroid hormones (THs), thyroxine (T4) and triiodothyronine (T3) in the blood of vertebrates. TH-binding sites are highly conserved in vertebrate TTR however, piscine TTR has a longer N-terminus which is thought to influence TH-binding affinity and may influence TTR stability. We produced recombinant wild-type sea bream TTR (sbTTRWT) plus two mutants in which six (sbTTRM6) and twelve (sbTTRM12) N-terminal residues were removed. Ligandbinding studies revealed similar affinities for T3 (Kd=10.6±1.7nM) and T4 (Kd=9.8±0.97nM) binding to sbTTRWT. Affinity for THs was unaltered in sbTTRM12 but sbTTRM6 had poorer affinity for T4 (Kd=252.3±15.8nM) implying that some residues in the N-terminus can influence T4 binding. sbTTRM6 inhibited acid-mediated fibril formation in vitro as shown by fluorometric measurements using thioflavine-T.In contrast, fibril formation by sbTTRM12 was significant, probably due to decreased stability of the tetramer. Such studies also suggested that sbTTRWT is more resistant to fibril formation than human TTR.